Al-Mundhir bin Al-Jaroud and brother Abdullah and their role in the Rashidun and Umayyad era(11-75AH-632-694AD) - الابراهيم يسرى (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
THE ABD al Qais tribe occupied an role befre Islam , It continued this role after the Islamic, It belonged to the AL-Jaroud family, which belonged to this tribe, Had an important role in the political and administrative existence in the Rashidun and Umayyad era, starting with Bishr bin Amr, Known as AL- Jaroud ,of AL-Mundhi and Abdullah . the subject of the research .AL-jaroud played an bringing pain to his tribe, Abd Al Qays, and his delegations, about the honor of the Holy Prophet Muhammad. He played arole in the Ridda Wars and some of the Persian conquests as the leader of Abd al –Qays, Al-Mundhir completed his career after leading the tribe in Basra and joined Ali bin Abi Talib. He fought on his side in the Battle of the Jamel and Siffin , but in the Umayyad era he moved to the side of the Umayyds until he died , His brother Abdullah came after him as the leader of the tribe and fought with the Umayyad against Kharijites, But the harsh policy of Al- Hajjaj Al –Thaqafi upon his arrival in Iraq forced Abdullah and those with him to revolt against Al- Hajjaj during ther war against the Khrijites, But his revolution failed and he died in it because the conditions for his revolution were not sufficient .